Analisis Implementasi Metode Etnomatematika Permainan Engklek terhadap Hasil Belajar Matematika Siswa Kelas III SD Negeri Sangiang III - Hidayat, Resti (Lembaga Yasin AlSys, 2022)
This study aims to describe the implementation of ethnomathematics of engklek games in grade III students at SDN Sangiang III and describe the ethnomathematic learning of engklek games on the learning outcomes of grade III students of SDN Sangiang III. This research uses qualitative research methods with a type of case study approach intended to accurately explain a phenomenon or characteristic of a particular individual, situation or group that occurs. The subjects in this study were grade III students of SDN Sangiang III with a total of one class of 58 students and took a sample of 30 students. The data collection technique uses observation with two sources, namely teachers and students, interviews with two speakers, namely teachers and students, and using document studies. The results of this study used ethnomathematics methods with engklek games which were considered effective for developing mathematics learning outcomes using engklek games.